Pengaruh Pandemı Covıd-19 terhadap Penjualan Suplemen Kesehatan dı Apotek “X” Kota Tarakan - Asma Lanuddin; Sari Wijayanti; Irma Novrianti; Dhea Erwina Suwanty (Journal Borneo, 2023)
The World Health Organization declared Coronavirus disease a pandemic in 2020. Two Indonesian citizens were confirmed to have Covid-19 when the virus was first detected. Panic buying in meeting daily needs is one of the impacts caused by Covid-19, especially health supplements such as vitamins or immunomodulators, due to a lack of understanding from the public. This study aims to determine the effect of Covid-19 on sales of health supplement products at the "X" pharmacy in Tarakan city. This research is analytic research which is observational in nature. The data was obtained from sales documents at the "X" pharmacy 12 months before and 12 months at the start of the Covid-19 pandemic. The health supplements taken for this study were Becom C®, Becom Zet®, and Imboost Force®. The data obtained were analyzed using paired T-test. The study results found that health supplements experienced an increase in sales of 314.41% - 808.42% with a P value = 0.038 for Becom C®, 0.039 for Becom Zet® and 0.011 for Imboost Force®. It can be concluded that Covid-19 has positively influenced the increasing sales of health supplement products at the "X" pharmacy in Tarakan city.